TGF-β1 signaling protects retinal ganglion cells from oxidative stress via modulation of the HO-1/Nrf2 pathway. (1st November 2020) - Chen, Hsin-Yi; Ho, Yi-Jung; Chou, Hsiu-Chuan; Liao, En-Chi; Tsai, Yi-Ting; Wei, Yu-Shan; Lin, Li-Hsun; Lin, Meng-Wei; Wang, Yi-Shiuan; Ko, Mei-Lan; Chan, Hong-Lin
Abstract: Oxidative stress provides a major contribution to the pathogenesis of glaucoma and may induce retinal ganglion cell (RGC) damage. Transforming growth factor β (TGF-β) has appeared as a neuroprotective protein in various indignities. However, the TGF-β mechanism of protective effects against oxidative stress damage in RGCs still undetermined. In our research, we investigated the regulatory mechanisms and potential effects of TGF-β1 & TGF-β2 in hydrogen peroxide (H2 O2 )-stimulated oxidative stress of RGCs in vitro . By a series of cell functional qualitative analysis, such as MTT cell viability assay, wound healing ability assay, apoptosis assay, intracellular ROS detection, immunoblot analysis, intracellular GSH content, and high-resolution respirometry, we illustrated the cell state in oxidative stress-induced injury. Results of protein expression showed that TGF-β1 & TGF-β2 was upregulated in RGCs after H2 O2 stimulation. Cell functional assays resulted that knockdown of TGF-β1 & TGF-β2 reduced survival rate whereas enhanced apoptosis and accumulation of reactive oxygen species (ROS). Especially TGF-β1 upregulation promoted the protein expression of aldehyde dehydrogenase 3A1 (ALDH3A1) and increased the activity of antioxidant and neuroprotection pathways. Additionally, TGF-β1 & TGF-β2 on antioxidant signaling was related to activation of heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor (Nrf2), which are stress-response proteins. ROS accumulation followed by the accumulation of hypoxia-inducible factor (HIF-1α) caused mitochondrial damage and led to neurodegeneration. In summary, our results demonstrated that TGF-β1 preserves RGCs from free radicals-mediated injury by upregulating the activation of Nrf2 expression and HO-1 signaling balance HIF-1α upregulation, implying a prospective role of TGF-β1 in retinal neuroprotection-related therapies. Highlights: TGF-β1 protected RGCs from H2O2-induced oxidative stress. ALDH3A1 upregulation may defend RGCs against oxidative injury. TGF-β1 enhanced the activation of Nrf2/HO-1/HIF-1α signal transduction. Pathway characterization of hydrogen peroxide-induced oxidative stress on RGCs.